Akhlak Manusia terhadap Dirinya, Allah SWT, dan Rasulullah SAW - Predi Ari Repi; Pangulu Abdul Karim (Transformasi Manageria Journal of Islamic Education Management, 2024)
The impact of ethical challenges in the era of globalization has become evident among the younger generation, leading to a reluctance among youth to incorporate Islamic guidance into their daily lives. This study aims to explore the application of human morality concerning oneself, Allah SWT, and Prophet Muhammad SAW. The research adopts a subjective approach with a focus on library research methods. Scientific references, including articles, books, proceedings, and academic projects (such as theses or dissertations), serve as the primary sources of research data. The findings reveal that personal morality involves striving to balance the physical and spiritual aspects of oneself without imposing limitations on either, while upholding virtues such as gratitude, sincerity, patience, forgiveness, and trust. Additionally, human morality towards Allah SWT as the Creator entails worship and the maintenance of the continuity of life as khalifatullah fil ardh. Regarding morality towards the Messenger of Allah, it involves emulating his life and implementing Islamic teachings in alignment with the Prophet Muhammad's words, actions, and judgments.